2008
DOI: 10.1051/agro:2008029
|View full text |Cite
|
Sign up to set email alerts
|

Sweet corn production and efficiency of nitrogen use in high cover crop residue

Abstract: -In the humid, temperate mid-Atlantic area of the USA, crop production that leaves the soil uncovered can lead to undesirable soil and nutrient losses to the surrounding Chesapeake Bay watershed. To cope with this issue, winter annual cover crops could provide soil cover both during winter months and, as surface residue in no-tillage cropping systems, during summer months. Legume cover crops such as hairy vetch can produce abundant biomass and N by the time summer crops are planted in spring. Although N minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
(31 reference statements)
2
29
1
Order By: Relevance
“…Adequate summer rainfall (Table 3) Higher plant available N during the sweet corn season at Ridgetown than Bothwell (Table 7) provides some explanation as to why cover crops affected sweet corn yield in the 0 kg N ha (1 but not the 140 kg N ha (1 treatment at Bothwell and why there was no cover crop effect with or without N fertilizer at Ridgetown. In general, the positive effect of N fertilizer on total and marketable yield at Bothwell, and in total yield at Ridgetown was consistent with other research (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002;Teasdale et al 2008). Similar to our study, Mullins et al (1999), Burket et al (1997), and Griffin et al (2000) observed variable weather during their studies, including hot dry years.…”
Section: Yield and Profit Marginssupporting
confidence: 92%
See 2 more Smart Citations
“…Adequate summer rainfall (Table 3) Higher plant available N during the sweet corn season at Ridgetown than Bothwell (Table 7) provides some explanation as to why cover crops affected sweet corn yield in the 0 kg N ha (1 but not the 140 kg N ha (1 treatment at Bothwell and why there was no cover crop effect with or without N fertilizer at Ridgetown. In general, the positive effect of N fertilizer on total and marketable yield at Bothwell, and in total yield at Ridgetown was consistent with other research (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002;Teasdale et al 2008). Similar to our study, Mullins et al (1999), Burket et al (1997), and Griffin et al (2000) observed variable weather during their studies, including hot dry years.…”
Section: Yield and Profit Marginssupporting
confidence: 92%
“…Similar to our study, Mullins et al (1999), Burket et al (1997), and Griffin et al (2000) observed variable weather during their studies, including hot dry years. As well, with the exception of the study by Teasdale et al (2008), which was conducted on loamy sand soil, the other studies (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002) occurred predominately on silt loam soils and therefore were less sandy than the soils in our study. Similar to our study, effects of cover crops on sweet corn yield showed mixed and often contrasting results depending on site-year (Carrera et al 2004;Malik et al 2008).…”
Section: Yield and Profit Marginscontrasting
confidence: 57%
See 1 more Smart Citation
“…Only for tomato marketable yield of 2009 and 2010 variations were clearly due to causes other than N availability: in 2009 it was conventional tomato that yielded less that potential due to a bad crop establishment; this because a 50 mm rainfall occurred during seedbed preparation impeding an adequate soil loosening which, on the contrary, could be obtained in the organic soil thanks to green manure biomass incorporated just before; in 2010 the marketable yield loss of organic tomato was due to an unsuccessful mechanical control of weed infestation and to a higher proportion of unmarketable fruits over conventional tomato (36% vs 20% of total fruit weight in ORG and LOW, respectively). A lower yield was reported in several studies where maize was grown organically (Mischler et al, 2010;Wortman et al, 2012) or fertilized by cover crops (Tonitto et al, 2006;Teasdale et al, 2008) and was often explained by the lower and variable N supply from green manures. In turn, the growth and Ndfa accumulation of green manures was affected by fall winter climate and was actually much variable.…”
Section: Discussionmentioning
confidence: 84%
“…These two crops differ much for N uptake capacity (also due to different plant spacing), total amount and timing of N need, effect of N on crop yield (also due to different requirements for marketable yield between a cereal and a vegetable). Maize is a high N demanding crop with early spring sowing and green manures may not guarantee an adequate N availability especially in early growth phases, with consequent lower growth and grain yield (Benincasa et al, , 2010Teasdale et al, 2008). Processing tomato may better use organic N sources in virtue of its lower and later N need due to its mid spring transplanting date .…”
Section: Introductionmentioning
confidence: 99%